Association between apolipoprotein B genetic polymorphism and the risk of calcific aortic stenosis in Chinese subjects, in Xinjiang, China - Wang, Yong-Tao (Lipids Health Dis, 2018)
BACKGROUND: Limited information is available when it comes to the impact of genetic on Calcific Aortic Stenosis (CAS). Apolipoprotein B (apoB) is a key component in lipid metabolism and plays an important role in the dynamic equilibrium of cholesterol. We performed a case–control study to explore the association of apoB genetic polymorphisms with CAS in Chinese subjects, in Xinjiang, China. METHODS: We designed a case-control study including 314 CAS patients and 652 age- and sex-matched control subjects. Using the polymerase chain reaction-restriction fragment length (PCR-RFLP) method, we genotyped two SNPs (rs6725189 and rs693) of apoB gene in all subjects. RESULTS: We found that the rs693 T allele was associated with a significantly elevated CAS risk [TT/CT vs. CC: adjusted odds ratio (AOR) = 1.58, 95% confidence interval (CI) = 1.82–2.10, P = 0.002] and the rs6725189 T allele was also associated with a significantly elevated CAS risk (GT vs. GG: AOR = 1.82, 95% CI = 1.14–2.92, P = 0.013). Furthermore, we also found that the TC levels were significantly higher in rs693 TT/CT genotypes than that in CC genotypes (P < 0.05). CONCLUSIONS: Both rs693 and rs6725189 of the apoB gene are associated with CAS in Chinese subjects, in Xinjiang, China.